TikTok Live Streaming as a Digital Marketing Communication Media - Abadi, Totok Wahyu; Ivoniasari , Oky (The Journal of Society and Media, 2024)
This research aims to analyze the digital marketing communication strategies carried out by influencers via TikTok Live Streaming. The basic concept used in this research is the SOSTAC Model of Digital Marketing Theory from PR Smith. This type of qualitative descriptive research uses as many as five informants who own TikTok accounts. Data collection techniques were conducted through in-depth interviews and observations of each informant's TikTok Live Streaming. Data analysis uses the Miles and Huberman interactive model. The research results showed that TikTok Live Streaming was used as a digital marketing communication medium. This feature makes it easier for consumers to get product information. Influencers play an important role in TikTok Live Streaming regarding consumer behavior, purchasing decisions, and purchase intentions. Influencers can build relationships with consumers, especially for businesses targeting millennial customers, while social media is used to encourage product engagement and brand loyalty. Influencers have credibility and understanding regarding the products of the brand they are communicating with. When doing live streaming, influencers need a strategy, tactics, action, and control to reach the target market more quickly. Digital marketing communication strategies can increase communication messages' effectiveness and help achieve communication goals.